Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1177/019459987908700317
|View full text |Cite
|
Sign up to set email alerts
|

Ossicular Abnormalities in Down's Syndrome

Abstract: Down's syndrome has been associated with hearing loss and otitis media. Because of difficulty in examination, however, there have been few detailed otologic studies on this population. An understanding of the nature and frequency of ear disease in Down's syndrome is important, since it is common and occurs in more than one in every 600 live births. To define the aural manifestations of Down's syndrome, complete otologic and audiometric examination was performed on 107 consecutive patients. This included micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 3 publications
2
32
0
1
Order By: Relevance
“…While Balkany et al [1979b] agreed with the need for aggressive medical and surgical management of middle ear infections, they found little improvement in conductive hearing loss in patients with DS who underwent reconstructive surgery for ossicular abnormalities. They suggested a more conservative course such as amplification in patients who continued to have a conductive hearing loss following treatment of their chronic ear disease [Balkany et al, 1979b].…”
Section: Hearing Lossmentioning
confidence: 84%
See 1 more Smart Citation
“…While Balkany et al [1979b] agreed with the need for aggressive medical and surgical management of middle ear infections, they found little improvement in conductive hearing loss in patients with DS who underwent reconstructive surgery for ossicular abnormalities. They suggested a more conservative course such as amplification in patients who continued to have a conductive hearing loss following treatment of their chronic ear disease [Balkany et al, 1979b].…”
Section: Hearing Lossmentioning
confidence: 84%
“…Answers to these questions are not yet published. Balkany et al [1979b] reported that 83% of the hearing loss seen in patients with DS was due to a 'conductive' or middle ear abnormality. Sixty percent of this conductive hearing loss was attributed to chronic ear disease such as middle ear infections or tympanic membrane perforations, and the other 0% was felt to be due to ossicular abnormalities with malformations found on temporal bone studies.…”
Section: Hearing Lossmentioning
confidence: 99%
“…Of the group of 22 children with Down syndrome, 8 children had normally ation during examination [1]. Abnormalities of the pinna are very common in Down syndrome [1].…”
Section: Resultsmentioning
confidence: 99%
“…Of the group of 22 children with Down syndrome, 8 children had normally ation during examination [1]. Abnormalities of the pinna are very common in Down syndrome [1]. It has been suggested that the hypotonia associated with Down syndrome may also affect the tensor veli palatini and cause Eustachian tube dysfunction [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation